2020
DOI: 10.1111/ajt.15576
|View full text |Cite
|
Sign up to set email alerts
|

Liver transplant for hepatocellular carcinoma in the United States: Evolving trends over the last three decades

Abstract: This is the author manuscript accepted for publication and has undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record. Please cite this article as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 30 publications
1
29
0
Order By: Relevance
“… 21 , 28 , 29 A recent study showed that diabetes was a predictor of decreased survival in the interferon era but not the direct-acting antiviral era, but the reasons for this are unclear. 30 Finally, it also appears that BCLC stage is important, as Su et al reported lower survival rates in HCC patients with diabetes and BCLC stage 0, A, and B, but no difference in survival seen in stages C and D. 31 , 32 …”
Section: Discussionmentioning
confidence: 99%
“… 21 , 28 , 29 A recent study showed that diabetes was a predictor of decreased survival in the interferon era but not the direct-acting antiviral era, but the reasons for this are unclear. 30 Finally, it also appears that BCLC stage is important, as Su et al reported lower survival rates in HCC patients with diabetes and BCLC stage 0, A, and B, but no difference in survival seen in stages C and D. 31 , 32 …”
Section: Discussionmentioning
confidence: 99%
“…( 36 ) Despite this, the proportion of LT due to HCC has steadily increased. ( 37 ) It remains a common indication for LT both in terms of wait‐list registrants and recipients (24% and 27% in 2015, respectively). ( 38 ) Considering the discrepancy between the number of recipients with HCC and the number of available organs and our lack of tools to accurately monitor tumor aggressiveness, it is imperative to develop new methods and better match patients with organs on an individual basis.…”
Section: Clinical Selection Criteria For Patients With Hccmentioning
confidence: 99%
“…The proposed mechanism of action of HBIg includes binding to the viral particles and HBsAg, resulting in neutralization and The viral envelope proteins, such as HBsAg, bind to host cell surface receptors, resulting in endocytosis of the hepatitis B virion into the host cell. 1 The nucleocapsid releases relaxed circular HBV DNA (rcDNA) into the nucleus,2 which is converted into covalently closed circular double stranded DNA (cccDNA). 3 The cccDNA is a template for transcription of viral RNA.…”
Section: Hbig Monotherapymentioning
confidence: 99%
“…In the USA, hepatocellular carcinoma (HCC) and liver failure due to hepatitis C are the most common indications for liver transplant (LT). 1 However, worldwide, hepatitis B virus (HBV) infection is the major risk factor for development of HCC, and has remained the leading indication for LT in Asian countries. 2 Until the 1990s, HBV infection was considered a relative contraindication to LT, due to high risk of graft infection and subsequent liver failure as a result of post-transplant immunosuppression.…”
Section: Introductionmentioning
confidence: 99%